Stoop sale treasure - Haydu, Corey Ann (Haydu, Corey Ann. Hand-me-down magic, 2020)
"Del loves LOTS of things! The Curious Cousins Secondhand Shoppe. Ginormous family dinners. And of course, her best-friend-cousin, Alma. Alma loves her abuelita's tasty empanadas. Her old home by the lake. And soon, she'll love living in the same place as her best-friend-cousin, Del. Yet despite having Del by her side, Alma isn't quite sure she fits in with their family at 86 1/2 Twenty-Third Avenue. It's a new life and it's all so different. When Del finds a special item at a neighbor's stoop sale, she gets so excited by the magic luck it brings--but doesn't see that it's driving the two best friends apart. Will family, friendship, and maybe a little everyday magic be enough to make things right again?" --